2009 16th International Conference on Digital Signal Processing 2009
DOI: 10.1109/icdsp.2009.5201124
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional FPGA architectures: A shift paradigm for energy-performance efficient DSP implementations

Abstract: Modern applications exhibit increased complexity which introduces extra constraints during implementation related to delay, power consumption and silicon area. This problem is even more important when we deal with Digital System Processor (DSP) kernels, as there are demands for even higher clock frequencies and logic densities, which cannot be satisfied with existing design technologies. Three-dimensional (3D) integration is an emerging technology that promises to alleviate problems related to performance impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…More info regarding the features of proposed methodology of application mapping under different design constraints (timing-aware, power-aware, etc) onto 3D FPGAs can be found in [9], [10], [11], [12].…”
Section: D Fpga Flowmentioning
confidence: 99%
“…More info regarding the features of proposed methodology of application mapping under different design constraints (timing-aware, power-aware, etc) onto 3D FPGAs can be found in [9], [10], [11], [12].…”
Section: D Fpga Flowmentioning
confidence: 99%
“…This architecture is called CNPGA in this paper. Considerable researches have been reported on separating the routing resources in many modern FPGA technologies, especially in three-dimensional chips [20]. CNFET-based routing switches in the proposed architecture may be fabricated on a CMOS wafer or can be constructed as an auxiliary layer in a threedimensional chip.…”
Section: The Proposed Hybrid Fpga Architecturementioning
confidence: 99%
“…In the context of GPPs, interface between the L2 cache and main memory is architected using 3D interconnect technology, and performance is compared to a 2D design for memoryintensive applications [6][7][8][9][10]. In the context of FPGAs, a number of recent studies have shown that 3D FPGAs have better performance than existing 2D designs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%